Identifikasi Spesies Hiu yang Tertangkap di Perairan Utara Aceh - Fredi Lesmana; Maria Ulfah; Rizwan Rizwan (Universitas Syiah Kuala, 2018)
Sharks have been international problems since 2013 after the emergence of several species of shark in Appendix II CITES status. This is due to the high exploitation of shark fishing, both as a target catch and as a by-catch. This study entitled the identification of shark species caught in the North Aceh Waters, which aims to identify the species of the shark located in the North Aceh Waters and to determine the conservation status of the shark species. The study was conducted at Pelabuhan Perikanan Samudera Lampulo (PPS Lampulo) for three months, starting from February 2017 to April 2017. The method used in this research is survey method and shark identification done by Rapid Assessment (rapid estimation), refers to the methods undertaken by Fahmi and White (2006). From the results of the observation, sharks identified as many as 747 individuals consisting of 16 families, 20 genus and 32 species of shark. Of these, there are several species included in the IUCN red list, i.e. 1 species with EN category (threatened), 10 species in the VU category (vulnerable), and 13 species in the NT category (Near Threatened). In addition, 4 shark species are categorized into Appendix II CITES status. Hiu telah menjadi permasalahan internasional sejak tahun 2013, setelah masuknya beberapa spesies hiu dalam status apendiks II CITES.Hal ini disebabkan oleh tingginya ekploitasi penangkapan hiu, baik sebagai tangkapan target maupun sebagai tangkapan sampingan.Penelitian ini berjudul identifikasi spesies hiu yang tertangkap di Perairan Utara Aceh, yang bertujuan untuk mengidentifikasi spesies hiu yang berada di Perairan Utara Aceh dan untuk mengetahui status konservasi spesies hiu tersebut.Penelitian dilakukan pada Pelabuhan Perikanan Samudera Lampulo (PPS Lampulo) selama tiga bulan, dimulai saat bulan Februari 2017 hingga April 2017.Metode yang digunakan dalam penelitian ini adalah metode survei dan identifikasi hiu dilakukan secara Rapid Assessment (pendugaan secara cepat), mengacu pada metode yang dilakukan oleh Fahmi dan White (2006). Dari hasil pengamatan, berhasil teridentifikasi sebanyak 747 individu terdiri dari 16 family, 20 genus dan 32 spesies hiu. Dari jumlah hiu tersebut terdapat beberapa spesies yang masuk dalam IUCN red list yaitu, 1 spesies dengan kategori EN (terancam), 10 spesies dengan kategori VU (rawan), dan 13 spesies dengan kategori NT (hampir terancam). Selain itu 4 spesies hiu masuk kedalam status Appendix II CITES.